The Dynamics of Climate Change and Environmental Security in Nigeria - Nwanegwo, Kelechi Christopher; Fajemoroye, James Oluwagbamigbe; Udochu, Eke; Dutra e Silva, Sandro (Fronteira: Journal of Social, Technological and Environmental Science, 2025)
Climate change and environmental security are ongoing challenges in Nigeria. This literature review explores the dynamics of climate change and environmental security alongside proposed solutions. The study employs qualitative research, primarily drawing on reports from international NGOs that address climate change and ecological security in Nigeria. It also utilizes content analysis based on literature, additional bibliographies, and published academic works. The results indicate that the issue of climate change in Nigeria still requires further exploration, as no reports provide in-depth investigations. However, they also show the emergence of debates concerning the problem in both the political and academic spheres. Regarding official documentation, they highlight that Nigeria has adopted policies aimed at significant domestic adaptations to international agreements and treaties to mitigate the effects of climate change. However, research indicates that these efforts have not effectively addressed the consequences of climate change, resulting in more significant environmental degradation. The article highlights the shortcomings in the ways government agencies and other institutions have addressed climate change in Nigeria, including legal and institutional limitations, corruption, and governance deficiencies.